Arylisoquinoline-derived organoboron dyes with a triaryl skeleton show dual fluorescence - Pais, Vânia F.; Neumann, Tristan; Vayá, Ignacio; Jiménez, M. Consuelo; Ros, Abel; Pischel, Uwe (Beilstein Journal of Organic Chemistry, 2019)
Four new dyes that derive from borylated arylisoquinolines were prepared, containing a third aryl residue (naphthyl, 4-methoxynaphthyl, pyrenyl or anthryl) that is linked via an additional stereogenic axis. The triaryl cores were synthesized by Suzuki couplings and then transformed into boronic acid esters by employing an Ir(I)-catalyzed reaction. The chromophores show dual emission behavior, where the long-wavelength emission band can reach maxima close to 600 nm in polar solvents. The fluorescence quantum yields of the dyes are generally in the range of 0.2–0.4, reaching in some cases values as high as 0.5–0.6. Laser-flash photolysis provided evidence for the existence of excited triplet states. The dyes form fluoroboronate complexes with fluoride anions, leading to the observation of the quenching of the long-wavelength emission band and ratiometric response by the build-up of a hypsochromically shifted emission signal.
Keywords: anions; dyes; fluorescence; laser-flash photolysis; organoboron